India Inc. 2050 - potential deviations from 'business-as-usual' - Verma, Shilp; Phansalkar, Sanjiv J. (2005)
Research comment on report of the National Commission on Integrated Water Resources Development (NCIWRD) titled ?Integrated water resource development: A plan for action.?